DAMPAK COVID-19 TERHADAP BIRO PERJALANAN DAN PENYELENGGARAAN HAJI DAN UMRAH - Edi Haskar (Ensiklopedia of Journal, 2021)
The Covid 19 outbreak has had a major impact on the world economy, where Indonesia is also experiencing it. With the limitation of all activities, it is very influential on economic stability. One of the economic aspects affected is the activities of the Travel Bureau and Hajj and Umrah Organizers. Where this Travel Bureau has been affected because of the absence of a permit for Hajj and Umrah services given by the Government of Saudi Arabia, to break the chain of the spread of Covid 19. With the cancellation of the departure of the Hajj and Umrah pilgrims, the travel agency also suffered losses, as well as concerns about the survival of its business. . However, some travel agencies carry out a strategy to survive by doing other types of business that can at least help sustain the business, such as carrying out export and import activities. Keywords: Covid 19, Impact, Travel Agency.